¿Cómo convertir y = 3x ^ 2-5x-y ^ 2 en una ecuación polar?

¿Cómo convertir y = 3x ^ 2-5x-y ^ 2 en una ecuación polar?
Anonim

Responder:

#r = - (sintheta + 5costheta) / (sin ^ 2theta-3cos ^ 2theta) #

Explicación:

Para esto necesitamos lo siguiente:

# x = rcostheta #

# y = rsintheta #

# rsintheta = 3 (rcostheta) ^ 2-5 (rcostheta) - (rsintheta) ^ 2 #

# rsintheta = 3r ^ 2cos ^ 2theta-5rcostheta-r ^ 2sin ^ 2theta #

# rsintheta + r ^ 2sin ^ 2theta = 3r ^ 2cos ^ 2theta-5rcostheta #

# sintheta + rsin ^ 2theta = 3rcos ^ 2theta-5costheta #

# rsin ^ 2theta-3rcos ^ 2theta = -sintheta-5costheta #

#r = (- sintheta-5costheta) / (sin ^ 2theta-3cos ^ 2theta) = - (sintheta + 5costheta) / (sin ^ 2theta-3cos ^ 2theta) #